Local leader survey instrument on women’s voice and agency in local governance in Nigeria - Adida, Claire; Arriola, Leonardo; Fisher, Rachel; Kosec, Katrina; Kyle, Jordan; Matanock, Aila; Mo, Cecilia H.; Adeyanju, Dolapo; Olanrewaju, Opeyemi (International Food Policy Research Institute, 2023)
This questionnaire was prepared by IFPRI. It is part of the CGIAR Research Initiatives on Gender Equality (HER+) and Fragility, Conflict, and Migration (FCM). We would like to thank all funders who supported this research through their contributions to the CGIAR Trust Fund: https://www.cgiar.org/funders.